Analysis of Video as Virtual Learning Media in Physics for High School Student - Fianti, Fianti; Givarin, Delvananta; Handayani, Langlang; Sugiyanto, Sugiyanto; Arifah, Husna (Universitas Negeri Semarang, 2025)
The use of technology in using the learning media becomes a matter for teachers because it plays an important role in achieving learning goals. Technology is applied in education as learning media videos in learning process in classroom. The research aims were (1) analysis the use, (2) finding the positive impacts, and (3) finding the inhibitor factors in learning videos as virtual learning media on physics subjects for high school students in Pacitan Regency. The study used a qualitative-descriptive method using the data-collection technique: centralized interviews. The results of the study revealed that (1) the way high school teachers teach media in Pacitan Regency was mostly the same, id est explaining the key points of the material that would be presented through the video, dividing students into small groups and allowing them to discuss and communicate with each other, as well as sharing ideas and thoughts with their group mates, and then concluded with a confirmation and a clarification of the students' conceptual understanding. (2) There were several positive impacts from the use of a learning video media that is helpful teachers and students in the teaching process, that is students became more interested in the lesson material presented, and students became more active due to the learning process using group discussion methods, which led to increase enthusiasm. (3) There were also several inhibitors from the use of learning video media, i.e. some teachers not being tech-capable, which likely caused difficulties in operating the tools and facilities and infrastructure provided by the school were still incomplete or might not have been available at all.